Implementation of Financial Accounting in Micro, Small, and Medium Enterprises in Manado City: A Qualitative Descriptive Study - Jeyfenshi Nayoan; Friska Langelo (Cattleya Darmaya Fortuna, 2026)
This study aims to describe the application of financial accounting in Micro, Small, and Medium Enterprises (MSMEs) in Manado City and to assess the extent to which these practices align with the Financial Accounting Standards for Micro, Small, and Medium Entities (SAK EMKM). The approach used was descriptive qualitative, with data collection techniques consisting of in-depth interviews and documentation studies of the financial records and reports of several MSMEs from various business types. The results indicate that most MSMEs still implement simple cash-based accounting, have not prepared complete financial reports, and have not consistently separated personal and business finances. Meanwhile, understanding of SAK EMKM remains low, resulting in the standard not being widely used as a reference. Supporting factors such as training, mentoring, and the use of simple financial applications have proven potential to encourage improvements in reporting practices, while the main obstacles stem from limited accounting literacy, time, and the perception that detailed record-keeping is an additional burden. Conceptually, this study emphasizes the importance of improving accounting understanding and gradually implementing SAK EMKM to produce more reliable financial information as a basis for decision-making and access to financing for MSMEs.